Ethical issues in organ transplantation. Issue 8 (August 2021) - Modra, Lucy; Hilton, Andrew
Abstract: Critical care clinicians are central to the organ transplantation process and therefore should be aware of the myriad ethical issues it raises. Organ donation can transform the lives of transplant recipients. However, it also warrants particular ethical scrutiny. Organ procurement is a procedure that cannot physically benefit the patient upon whom it is performed. Moreover, the potential donor incapacitated by terminal illness is usually unable to actively consent to donation. This article reviews contemporary debates in vital organ transplantation, including the definition of death, perimortem interventions and research, and merits of 'opt-in' versus 'opt-out' donor registries.